Análisis de los contenidos ecológicos en radio de La Provincia de Los Ríos - Villegas Guizado, Kevin Josué (2020)
The present research work was carried out with the objective of analyzing the ecological contents in radio of the Province of Los Ríos, in order to publicize the programs that deal with ecological issues since they are very important in our society and the world, although Most of the radio stations in the city of Babahoyo handle more of a current news structure. They carry out reports as well as live interviews. Some of these radio programs such as free radio stands out in the social aid news, which also focuses on guiding and educating and raising awareness of Riosense citizens. The techniques used in this work were through the qualitative modality that which is based on observation and open interviews for its subsequent definition, having a clear objective of analyzing its content. The social networks and web pages of radio stations in Babahoyo with greater tuning were also investigated, where a lot of essential information was released for the topic of interest, which is ecological content. The contents of radio programs in the province of Los Ríos, specifically in the city of Babahoyo, capital capital of the province, generate little environmental content, thanks to this ecological awareness is not promoted in the citizens of Rio de Janeiro, on the other hand, they do not generate that level of consciousness in people since there is very little ecological content and they give little interest.